Document Storage Needs Analysis of Medical Record Rack and Spacious Room in Clinical Pertamedika Main Hall - Ervina Ervina; Vela Jeriatin (Green Publisher Indonesia, 2021)
Storage rack is one of the hospital equipment that functions to store medical record documents with the availability of medical record document storage racks in accordance with the storage capacity of medical record documents, there will be no buildup of documents on the floor. This study aims to determine the number of shelves needed for storing medical records of patients at the Pertamedika Pendopo Main Clinic in 2021. This research used a quantitative descriptive method by describing the results of the research and comparing it with the theory then conclude it. The study was conducted in June 2021 at the Pertamedika Pendopo Main Clinic. The population and sample used are storage shelves and all patient medical record documents. The instruments used in data collection include observation and interviews. The results of this study indicate that the number of visits of all patients at the Pertamedika Pendopo Main Clinic in 2020 was 5,197. The number of storage shelves needed at the Pertamedika Pendopo Main Clinic in 2021 amounted to 35 storage shelves with a length of 103 cm and a height of 224 cm. And the amount of space needed to accommodate 35 storage racks with a space between 90 cm and a distance of 150 cm is a room area of 157.59M ^ 2 with a length of 15.3 m and a width of 10.3 m. So that the shelf needed can be fulfilled and can accommodate all the patient's medical record documents systematically and does not complicate the officer in the process of storing and searching the patient's medical record document.